PRINCIPAL'S LEADERSHIP STRATEGY IN IMPROVING EDUCATION QUALITY - Tofhan Mamonto; Arkam Lahiya; Amaludin Bahansubu (International Journal of Teaching and Learning, 2025)
Principals' leadership strategies in improving the quality of education describe the efforts and approaches taken by principals to advance the quality of education in their institutions. The main focus of this research is on participatory and collaborative leadership strategies, professional development for teachers and staff, and policy evaluation and monitoring. Through inclusive leadership and involving various parties, the principal can create a conducive and harmonious school environment. Furthermore, developing the skills and competencies of educators through various trainings and workshops is an important factor in creating quality learning. Finally, the implementation of a continuous evaluation system allows the school to identify and improve sub-optimal aspects of the education process. With these strategies, this study highlights the crucial role of school principals in improving the quality of education in their schools.